EFFICIENT IOT BASED WBAN USING NOVEL ENERGY CLOSENESS BASED ROUTING MECHANISMS - Vijaya Karthik S V (International Journal of Innovations in Engineering Research and Technology, 2021)
Wireless Body Area Networks (WBAN) is defined as an emerging and a necessity solution to fulfil the needs of remote health related issues and remote monitoring of the health parameters. The health related datas from the elderly persons or the patients can be passed to the medical server and thereby the medical data can be monitored by the doctor remotely and providing the required medical prescriptions. In this WBAN, while transferring the data, the security is an important parameter to be considered and the priority of the data to be transferred is on high consideration as the data is related to medical field. There are variety of challenges that have been faced with the data transfer from patient to the medical server and the data transfer from doctor to the patient. To the overcome those challenges, the cache prediction and replacement algorithm for maximizing the cache utilization is proposed in this research. Also, the hash code computation technique is adopted to have the trustworthy of data. i.e., for the security of data transfer between the servers. At last, energy based efficient routing for the data transmission, energy closeness-based routing algorithm is suggested in this research.